Pendidikan Agama Islam dan Problematikanya di Sekolah - Siswoyo (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2018)
The problems and challenges that exist in Islamic Religious Education both in learning and in its application are multidimensional. Everything must have problems that become problems and challenges that must be faced and solutions are sought, especially in education. There are so many problems in education that still need to be solved. The author wants to examine specifically about the problems and challenges in Islamic Religious Education. There have been many studies on the problems of Islamic Religious Education, but they are still focused only on educators and school management. Even though the problem of Islamic Religious Education is not only in an educational institution but is a problem for all elements of society, including the family. In this study the author wants to discuss and examine the problems of Islamic Religious Education in terms of the scope of education, namely schools, families and communities. This study uses a qualitative method, based on a literature study. Hopefully this article is useful and can provide solutions to the problems that pose challenges in Islamic Religious Education as a scientific discipline, institution or way of life in the life of every human being, because religion is God's culture.